1966
DOI: 10.1111/j.1365-2672.1966.tb03484.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Disinfection of Hospital Woollen Blankets in Laundering

Abstract: SUMMABY. Three lamdry disinfecting processes for woollen blankets were tested in a hospital lamdry against total bacteria. Results were somewhat indefinite owing to a low general level of infeation and the incidence of slight recontamination during drying. Before drying, disinfection was demonstrated. Laboratory simulated launderings on pieces of blanket infected with Pseudomonas pyocyanea showed significant difFerences between the processes. ND P, P PI The figures quoted were selected at random from a larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1967
1967
1967
1967

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Formaldehyde a t 0.375% w/v was even more effective, whether it was used in the last rinse or in the penultimate rinse ( Table 2). Covered drop tests (Dickinson et al, 1962) showed no significant evidence of inhibition of growth on the plates by the residual formaldehyde.…”
Section: Disinfection In Launderingmentioning
confidence: 87%
See 4 more Smart Citations
“…Formaldehyde a t 0.375% w/v was even more effective, whether it was used in the last rinse or in the penultimate rinse ( Table 2). Covered drop tests (Dickinson et al, 1962) showed no significant evidence of inhibition of growth on the plates by the residual formaldehyde.…”
Section: Disinfection In Launderingmentioning
confidence: 87%
“…The Standard Washing Process described previously (Dickinson et al, 1962) was used as a typical laundering procedure. The disinfection process consisted simply of adding the formaldehyde to the penultimate or ultimate rinse extended t o 14 min.…”
Section: Disinfection In Launderingmentioning
confidence: 99%
See 3 more Smart Citations